Effects of channel widths, thicknesses of active layer on the electrical and photosensing properties of the 6,13-bis(triisopropylsilylethynyl) pentacene transistors by thermal evaporation method: Comparison study - Yakuphanoğlu, Fahrettin; Gunduz, Bayram (Elsevier Science Sa, 2012)
TIPS-pentacene transistors were fabricated using thermal evaporation technique with different thicknesses of the active layer (TIPS-pentacene) and various channel widths deposited on SiO2 layer and compared the performance and photo characteristics of TIPS-pentacene (300 nm) and (135 nm) transistors. In present review, we report the photoresponse performance of the pentacene thin-film transistors including various channel widths and active layer thickness. The performance and photo characteristics of the TIPS-pentacene (300 nm) and (135 nm) transistors were investigated under dark and white light illuminations and analyzed the effects of the channel widths and thickness of active layer on the electrical characteristics of the TIPS-pentacene transistor. The interface states of the TIPS-pentacene thin-film transistors were investigated. The photocurrent mechanism of the transistors was also discussed. Some important morphology parameters of the TIPS-pentacene thin film such as roughness and grain size were determined. The electrical and photosensing parameters of the TIPS-pentacene transistor such as mobility, threshold voltage, sub-threshold swing value, photosensitivity, photoresponse, I-on/I-off ratio, interface trap density, total trap density and photoresponsivity under dark and white light illuminations were determined. It was found that the channel width and active layer thickness of the pentacene transistors play an imporant role on the photoresponse of the pentacene transistors. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Effect of channel width; Photoresponsivity; TIPS-pentacene transistor